Prospects of direct detection of 48V gamma-rays from thermonuclear supernovae. Issue 2 (23rd September 2021) - Panther, Fiona H; Seitenzahl, Ivo R; Ruiter, Ashley J; Siegert, Thomas; Sim, Stuart; Crocker, Roland M
ABSTRACT: Detection of gamma-rays emitted by radioactive isotopes synthesized in stellar explosions can give important insights into the processes that power transients such as supernovae, as well as providing a detailed census of the abundance of different isotope species relevant to the chemical evolution of the Universe. Observations of nearby supernovae have yielded observational proof that 57 Co powered the late-time evolution of SN1987A's light curve, and conclusive evidence that 56 Ni and its daughter nuclei power the light curves of Type Ia supernovae. In this paper, we describe the prospects for detecting nuclear decay lines associated with the decay of 48 V, the daughter nucleus of 48 Cr, which is expected to be synthesized in large quantities – $M_{Cr}\sim 1.9× 10^{-2}\, \mathrm{M_\odot }$ – in transients initiated by explosive helium burning (α-capture) of a thick helium shell. We calculate emergent gamma-ray line fluxes for a simulated explosion model of a thermonuclear explosion of carbon–oxygen white dwarf core of mass $0.45\, M_{\odot }$ surrounded by a thick helium layer of mass $0.21\, M_{\odot }$ . We present observational limits on the presence of 48 V in nearby SNe Ia 2014J using the INTEGRAL space telescope, excluding a 48 Cr production on the surface of more than $0.1\, \mathrm{M_{\odot }}$ . We find that the future gamma-ray mission the All-Sky Medium Energy Gamma-Ray Observatory (AMEGO) will have an approximately 5 per cent chance of observing 48 V gamma-rays from such events during the currently planned operational lifetime, based on our birthrate predictions of faint thermonuclear transients. We describe the conditions for a 3σ detection by the gamma-ray telescopes INTEGRAL /SPI, Compton Spectrometer and Imager (COSI), and AMEGO.